2017
DOI: 10.1016/j.dci.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

High levels of eukaryotic Initiation Factor 6 (eIF6) are required for immune system homeostasis and for steering the glycolytic flux of TCR-stimulated CD4+ T cells in both mice and humans

Abstract: Eukaryotic Initiation Factor 6 (eIF6) is required for 60S ribosomal subunit biogenesis and efficient initiation of translation. Intriguingly, in both mice and humans, endogenous levels of eIF6 are detrimental as they act as tumor and obesity facilitators, raising the question on the evolutionary pressure that maintains high eIF6 levels. Here we show that, in mice and humans, high levels of eIF6 are required for proper immune functions. First, eIF6 heterozygous (het) mice show an increased mortality during vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Value of the data Albeit preserving precise levels of eIF6 is of physiological importance [1] , [2] , [3] , [4] , [5] , [6] , our data indicate that eIF6 depletion does not alter the proportions of specific innate and adaptive immune system cell subpopulations nor the capability of the thymus to correctly produce mature thymocytes. These data could be a useful starting point for further characterization of the role of eIF6 and of translation in general in immune system regulation.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Value of the data Albeit preserving precise levels of eIF6 is of physiological importance [1] , [2] , [3] , [4] , [5] , [6] , our data indicate that eIF6 depletion does not alter the proportions of specific innate and adaptive immune system cell subpopulations nor the capability of the thymus to correctly produce mature thymocytes. These data could be a useful starting point for further characterization of the role of eIF6 and of translation in general in immune system regulation.…”
mentioning
confidence: 75%
“… The data described in this article are related to “High levels of eukaryotic Initiation Factor 6 (eIF6) are required for immune system homeostasis and for steering the glycolytic flux of TCR-stimulated CD4 + T cells in both mice and humans” (Manfrini et al, in press) [1] . eIF6 is a translation initiation factor required for ribosomal biogenesis (Sanvito et al, 1999) [2] and for proper translational initiation (Gallo and Manfrini, 2015; Miluzio et al, 2016) [3] , [4] whose protein abundance requires tight regulation.…”
mentioning
confidence: 99%
“…Eukaryotic initiation factor 6 is a powerful ribosome-associated factor that performs two functions: it acts as an essential trans-actor factor in the generation and quality control of 60S subunits [15,51] and as a translation factor in the cytoplasm. eIF6 is essential for efficient growth factor-stimulated translation [16,17,[24][25][26][52][53][54]. It is assumed that the biological activity of eIF6 resides in its capability to bind in a regulated fashion 60S ribosomal subunits, as it was shown originally by biochemical studies [14] and later confirmed by structural work [55].…”
Section: Discussionmentioning
confidence: 98%
“…The segment 8 sequence is only present in Cypovirus 14 isolates and seemed to be an autapomorphy for this species complex. We found a domain in the S8 segment related to the eukaryotic initiation factor 6 (eIF6), associated with protein translation (Manfrini et al, 2017). The impact and the function of each segment is not clear for most of the described CPVs so far.…”
Section: Discussionmentioning
confidence: 99%